A mycotic aortic aneurysm treated by thoracic endovascular aneurysm repair. Issue 11 (4th November 2019) - Tokuda, Takahiro; Tamaki, Mototsugu; Kitamura, Hideki; Koyama, Yutaka; Sawada, Koshi; Kawaguchi, Yasuhiko; Konakano, Kazuya; Okawa, Yasuhide
Abstract: An 88-year-old man was admitted with general fatigue. Computed tomography (CT) showed a descending aortic aneurysm. The laboratory data indicated severe infection. Despite negative blood cultures, broad-spectrum intravenous antibiotic therapy was started. Though antibiotic therapy was continued for about 2 weeks, the aneurysm extended 20 mm. Thoracic endovascular aortic repair was performed, and antibiotic therapy was continued for 4 weeks after the procedure, followed by oral antibiotics for 1 year. CT showed regression of the aneurysm 15 months after reconstruction. Antibiotic therapy, preoperatively and postoperatively, is important for a mycotic aortic aneurysm.